A novel review on various energy efficient routing algorithms in wireless sensor networks - Jain, Abhilasha; Kumar Goel, Ashok (International Journal of Engineering and Technology, 2018)
In the past few decades, Wireless sensor networks have exhibited a significant amount of growth and have been used in various applications like traffic control, environment monitoring etc. It comprises an accumulation of sensor nodes that sense the data from their surroundings and relay it to the base station. The network suffers from the limited energy constraints since the sensor nodes are mobile nodes and they run out of battery after a considerable amount of time. To overcome this, a certain level of heterogeneity is introduced among the nodes in terms of energy consumption to sustain the overall network lifetime. Various protocols are developed to prolong the network longevity. Among those, PEGASIS (Power-Efficient Gathering in Sensor Information Systems) and LEACH (Low- Energy Adaptive Clustering Hierarchy) are the significant ones, which ensures power-efficient gathering of the data in the sensor networks. This paper attempts to discuss the different aspects of PEGASIS and LEACH and their advantages and disadvantages in detail.